The importance of digitalization and innovation in small and medium enterprises - Syzdykova А.; Zhetibayev Ж. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2024)
Small and Medium-Sized Enterprises (SMEs) are structures that form the backbone of the global economy and play an important role in creating employment. In today’s rapidly changing and digitalizing world, it is critical for SMEs to invest in digital transformation and innovation to ensure their competitiveness and sustainability. This article examines the importance of digitalization and innovation in SMEs and the effects of these processes on businesses. Digitalization enables businesses to transform their business processes and increase their efficiency by using digital technologies. In particular, technologies such as cloud computing, artificial intelligence, the internet of things and big data analytics enable SMEs to reduce operational costs, improve customer experiences and develop more flexible business models. Digitalization also allows businesses to improve their marketing strategies and expand into new markets. Innovation is another critical factor for SMEs to gain competitive advantage. This article discusses the strategies and practices necessary for SMEs to successfully manage their digitalization and innovation processes. Additionally, the opportunities and challenges that digitalization and innovation offer to SMEs are also discussed. As a result, SMEs’ adoption of digitalization and innovation is essential for long-term success and sustainable growth.